THE QUALITY OF UNDERGRADUATE AND POSTGRADUATE TRAINING OF A TEACHING ASSISTANT - Michalík, Jan; Langer, Jiří (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the results of research, monitoring the attitudes of specific pedagogical staff – teaching assistants (TA) – in the Czech Republic to their undergraduate and postgraduate education. It includes statements of more than 800 respondents. It evaluates the qualifications, teaching assistants´ skills of working with children of the target group (disablements and social disadvantages). It provides a comparison of attitudes of both teaching assistants´ groups (acting as teaching assistants in two mentioned groups of pupils). It answers the questions: Which qualifications are regarded by TA as the most important? Which skills have not been provided by existing training programs and courses? How do they assess the conditions of executing the profession in schools? The research confirmed the difference between legislatively determined mandatory minimum of educational curriculum for TA and their real needs. It makes proposals to modify training programs.